Ophthalmic Manifestations of Hematopoietic Malignancy - Natsuyo Yoshida-Hata; Naomichi Katai; Toshiyuki Oshitari (Case Reports in Ophthalmological Medicine)
Purpose. To report the ocular findings in patients with hematopoietic malignancy with optic nerve involvement and abducens nerve palsy. Methods. The medical records of all cases of hematopoietic cancer with ophthalmic involvements seen in the Department of Ophthalmology of the National Center for Global Health and Medicine between 2009 and 2014 were reviewed. Results. Eight patients with hematopoietic cancer with optic nerve invasion or abducens nerve palsy were studied. The primary diseases were 3 cases of multiple myeloma, 1 case of acute lymphocytic leukemia, 1 case of follicular lymphoma, and 3 cases of AIDS-related lymphoma. Six cases had optic nerve invasion, 2 cases had abducens nerve palsy, and 1 case had optic nerve invasion of both eyes. The median visual acuity of eyes with optic nerve invasion was 0.885 logarithm of the minimum angle of resolution (logMAR) units. The final visual acuity of eyes with optic nerve invasion was 1.25 logMAR units, and that of those with sixth-nerve palsy was −0.1 logMAR units. Six cases died during the five-year follow-up period. An ophthalmic involvement in patients with hematopoietic cancer, especially AIDS-related lymphoma, was associated with poor prognosis. Conclusion. Because ophthalmic involvement in patients with hematopoietic malignancy has a poor prognosis, an early diagnosis of the cancers by the ophthalmologic findings by ophthalmologists could improve the prognosis.